Genetic instability and strain degeneration in Streptomyces rimosus. - Gravius, B (1993)
During a strain selection program to improve oxytetracycline production in Streptomyces rimosus R6, isolates that showed extreme morphological instability appeared. Propagation via spores gave much higher instability than did propagation via mycelial fragments. Five phenotypic traits were affected: sporulation, pigmentation, colony morphology, oxytetracycline production, and oxytetracycline resistance. The variants were classified on the basis of oxytetracycline resistance into three classes. Class I variants (99% of variants) showed parental levels of resistance but were very heterogeneous regarding the other phenotypes. No DNA rearrangements were detected in primary class I variants. Class II variants (1% of variants, oxytetracycline sensitive) were phenotypically uniform, and most variants carried the same large deletion of ca. 455 kb, including the oxytetracycline resistance gene otrB. Class III variants (0.1% of variants, increased oxytetracycline resistance) were phenotypically uniform and overproduced a brown pigment and oxytetracycline. Most of these variants also showed a reproducible large-scale DNA rearrangement, which probably included deletion and a low-level reiteration (three or four copies) of a DNA fragment. "Revertants" of some class I variants show a similar DNA rearrangement to the class III variants, but there is extensive reiteration of sequences of about 200 kb, including the otrB gene. The significance of these results for the problem of strain degeneration and overproduction of antibiotics is discussed.